2015
DOI: 10.1038/srep15363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scorpion venom peptide B5 on hematopoietic recovery in irradiated mice and the primary mechanisms

Abstract: Scorpion venom peptide B5 (SVP-B5) stimulates recovery of hematopoiesis after exposure to radiation. However, its radioprotective effects and mechanisms are still unclear. The aim of this study was to investigate the effects of SVP-B5 on hematopoietic recovery in mice after total body irradiation (TBI) at a dose of 7.5Gy and 6Gy and to explore the possible primary mechanisms. SVP-B5 at a dose of 2.63 μg/kg significantly reduced the mortality rate of mice after TBI (p < 0.05). It showed markedly protective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The sequence of the SVP-B5 peptide has been previously discussed (10). Using the Basic Local Alignment Search Tool protein database (https://blast.ncbi.nlm.nih.gov/Blast.cgi), it was found that SVP-B5 shares >80% homology with the sequence of the α-toxins family (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The sequence of the SVP-B5 peptide has been previously discussed (10). Using the Basic Local Alignment Search Tool protein database (https://blast.ncbi.nlm.nih.gov/Blast.cgi), it was found that SVP-B5 shares >80% homology with the sequence of the α-toxins family (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Our laboratory is continuously working on characterizing components from SVP and defining their effects on the post-radiation recovery of hematopoietic cells. The novel principal component SVP-B5 was isolated from the previously defined SVPII fraction (10). It was demonstrated that SVP-5B has hyperproliferative effects on irradiated hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations